اكتشاف منطقة رأس الفخذ في الصور فوق الصوتية للورك باستخدام تقنيات معالجة الصور الرقمية - حاتم, إياد (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم هذا البحث طريقة جديدة لتحديد منطقة رأس الفخذ في عينات صور فوق صوتية مأخوذة لمنطقة الورك للأطفال وذلك باستخدام تقنيات معالجة الصور الرقمية. حيث يمثل هذا الاكتشاف مرحلة مهمة في بناء نظام تشخيص مؤتمت للاكتشاف المبكر لحالة العسر التطوري للورك عند الأطفال (الخلع الوركي). تتم عملية التحديد على مرحلتين: المرحلة الاولى وتتضمن عمليات معالجة ابتدائية للصور للوصول إلى تقطيع للصورة ينتج عنها صور ثنائية تحوي مجموعة من الكائنات من ضمنها منطقة رأس الفخذ. وفي المرحلة الثانية تستخدم طريقة تحويل هاف التكراري العشوائي للتعرف على كائن منطقة الفخذ. بينت النتائح فعالية تقنيات معالجة الصور في تحديد منطقة رأس الفخذ في الصور فوق الصوتية مما يمهد لإمكانية بناء نظام التشخيص المؤتمت لحالة العسر التطوري للورك عند الأطفال. This paper presents a new method to detect the femoral head area in samples of ultrasound images taken of the hip area for children, using digital image processing techniques. This discovery is an important stage in building a promised automated diagnostic system for early detection of the developmental dysplasia of the hip cases in children. The process of detection is implemented in two stages: the first stage includes image processing operations to segment images which outputs binary images containing a collection of objects, including the femoral head area. In the second stage, Iterated Randomized Hough Transform is used to identify the object of femoral head area. Final results showed the effectiveness of image processing techniques to detect the femoral head area ​​in ultrasound images. It also showed the possibility of building a diagnosis automated system for developmental dysplasia of the hip in children.